Cement Pastes and Mortars Containing Nitrogen-Doped and Oxygen-Functionalized Multiwalled Carbon Nanotubes. (28th February 2016) - Martínez-Alanis, Mauricio; López-Urías, Florentino
Abstract : Cement pastes and mortars based on ordinary Portland cement containing nitrogen-doped multiwalled carbon nanotubes (MWCNT-N x ) or oxygen-functionalized multiwalled carbon nanotubes (MWCNT-O x ) are investigated. To incorporate MWCNTs into the cementitious matrix, the as-produced carpets are dispersed over periods of 1 and 2 hours in distilled water at pH levels of 1 and 7. The cement pastes are prepared by adding 0.1 wt% of MWCNTs to cement powder, followed by characterization with SEM and X-ray diffraction (XRD) at an early age (first hours of hydration). The mortars are mechanically characterized during the hydration process for a period of 28 days. SEM characterization of cement pastes revealed that the carbon nanotubes are well incorporated in the cementitious matrix, with the hydrated cement grains interconnected by long carbon nanotubes. XRD characterizations demonstrated that, during the hydration of cement pastes, different peaks emerged that were associated with ettringite, hydrated calcium silicate, and calcium hydroxide, among other structures. Results of the compressive strength measurements for mortars simultaneously mixed with MWCNT-N x and MWCNT-O x reached an increment of approximately 30% in compressive strength. In addition, density functional theory calculations were performed in nitrogen-doped and oxygen-functionalized carbon nanotubes interacting with a cement grain.